Analisis Pertimbangan Hakim Dalam Perkara Cerai Gugat Kumulasi Hutang dan Harta Bersama Perspektif KUHPerdata Dan KHI (Studi Putusan Nomor 592/Pdt.G/2024/PA.Jmb) - Alfarisi, Salman (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study examines decision number 592/Pdt.G/2024/PA.Jmb in a divorce case involving the accumulation of debts and joint property, focusing on the judge's considerations in deciding the case, which covers divorce, and the division of property and debts. It analyzes the legal provisions in decision number 592/Pdt.G/2024/PA.Jmb regarding the accumulation of debts and joint property according to the Civil Code and the Compilation of Islamic Law, as well as the legal consequences arising between the plaintiff and the defendant. This study uses a case study approach with a library research method, utilizing the Supreme Court's decision directory and related legal sources (Compilation of Islamic Law, Marriage Law, Civil Code). The data analysis technique uses analytical descriptive methods, specifically by identifying and classifying legal data, describing the content of Decision Number 592/Pdt.G/2024/Pa.Jmb, and assessing the conformity of the judge's considerations with the Compilation of Islamic Law (KHI), the Marriage Law, and the Civil Code. The research analysis results indicate that the judge's considerations in deciding case number 592/Pdt.G/2024/PA.Jmb involve several aspects that are juridical, philosophical, and sociological, so that the decision on the cumulative lawsuit of divorce with joint assets and debts is appropriate, from both the Civil Code and KHI perspectives. In addition to dissolving the marital relationship, the decision proportionally divides joint assets between the Plaintiff and the Defendant, while the responsibility for Briguna debt is fully imposed on the Defendant.   Keywords: Divorce Filing, Decision, Joint Property, Joint Debt.